Memoria de noticias 2019 : Oficina de Divulgación y Comunicación - Vicioso, M.; Navarro, Joan; Coll, Marta; Gili, Josep Maria; Santín, Andreu; Marrasé, Cèlia; Pelegrí, Josep Lluís; Piferrer, Francesc; Blázquez, Mercedes; Giménez, Joan; Villanueva, Roger; Simó, Rafel; et al. (CSIC - Instituto de Ciencias del Mar (ICM), 2019)
[EN] 37 publicated news 33 press releases sent to media and 4 news published online at the web. *Every press release is also published at the web. [.] - Are fisheries affecting seabird juvenile survival during the first days at sea? Joan Navarro, Marta Coll - Fishermen and scientists recover 450 gorgonians in Cap de Creus thanks to ResCap project, Josep María Gili, Andreu Santín - More than 700 experts in ecology meet at the 1st SIBECOL congress, Celia Marrasé - MITICAP, a collaboration project between scientists and fishermen, concludes, Josep María Gili, Andreu Santín - The Mediterranean Center for Marine and Environmental Research covers it frontside with art, Josep Lluís Pelegrí - ICM researchers participate in the book Sex Control in Aquaculture, Francesc Piferrer, Mercedes Blázquez - High levels of organophosphorus flame retardants and plasticizers in marine mammals, Joan Giménez - Global models underestimate impacts from climate extremes events, Marta Coll - The ICM works on ethics with the course “Biology and Care of Cephalopods”, Mercedes Blázquez, Roger Villanueva - Rafel Simó gets an Advanced Grant in the last ERC call, Rafel Simó - Importance of toothfish in the diet of generalist subantarctic killer whales, Joan Giménez - Climate change and biological invasions: perspective of artisan Mediterranean fishermen, Joaquim Garrabou - Hundreds of students participate in the III Congress of Young Oceanographers at the Institut de Ciències del Mar, Carine Simon - Marine protected areas in front of climate change: challenges and opportunities, Joaquim Garrabou - Ocean warming could cause an important decline in global marine species at the end of the century, Marta Coll - Tribute to Josefina Castellví, pioneer antarctic scientist - ICM scientists describe the epigenetic mechanisms underlying the onset of animal domestication, Dafni Anastasiadi, Francesc Piferrer - What to do if you are stung by a jellyfish, Josep María Gili - ICM-CSIC and The National Space Science Centre (NSSC-CAS) from China sign an ...